(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The important factor in the success of construction projects is its ability to objective estimate of the cost of the project and adapt to the changes of the external environment, which is affected by a lot of elements and the requirements of the competitive environment. The faces of those projects are several problems in order to achieve particular goals. To overcome these difficulties has been the development of research in the last two decades and turn the focus on the role of the cost of project management, by providing information and assist management in planning and control of the budget among the main elements of the project, namely, (time-cost-quality),The research aims at the possibility of developing and implementing mechanisms to rationalize the cost of using modern methods in the projects of the management style fast-track, which is a rapid technique for the stages of construction of the project in terms of the possibility of initiating implementation before the actual completion of the design phase through the project life cycle and is based on the premise of search that the construction project cost management based on the mechanism of the rapid implementation approach, leading to the reduction of time and rationalize costs and improve quality by using modern cost management tools throughout the project life cycle. Research has stamped a set of conclusions and recommendations of the most important was that the use of cost management in government units has become a prerequisite to according to modern trends in the preservation of the state’s resources and control over the performance, as well as the need for a modern methods in the implementation of projects and of style fast-track for the completion of projects in the shortest possible time and less expensive without compromising quality